Answer:
The option A i.e. [tex]k(x)=2^x[/tex] gives the formula for [tex]k(x) = (g-h)(x)[/tex]
Step-by-step explanation:
Given the two exponential functions:
As
[tex]k(x) = (g-h)(x)[/tex]
[tex]k(x)= g(x)-h(x)[/tex].......[A]
As
[tex]g(x)=3(2^x)[/tex] and [tex]h(x)=2^{x+1}[/tex]
So, putting the values of [tex]g(x)=3(2^x)[/tex] and [tex]h(x)=2^{x+1}[/tex] in equation [A]
[tex]k(x)=g(x)-h(x) \\[/tex]
[tex]\\ =3(2^x)-2^{x+1}[/tex]
[tex]=3(2^x)-2(2^{x}) \\[/tex]
[tex]\\ =2^x(3-2)[/tex]
[tex]=2^x[/tex]
Hence, the option A i.e. [tex]k(x)=2^x[/tex] gives the formula for [tex]k(x) = (g-h)(x)[/tex].
Keywords: function, exponential function
Learn more about exponential from brainly.com/question/733144
#learnwithBrainly